(untitled) (Estudios Sociales, 2024)
In this article we seek to understand the action of the metallurgical leader Augusto Vandor around the failed return of Juan Perón to Argentina in December 1964. To do so, we present the bibliography that found him responsible for the failure, and the bibliography which tried to review that accusation. We recovered various testimonies, periodical publications and archival material to try to place Vandor in the context of the return. From the intersection of these materials, we aspire to rethink some aspects of the peronism, as well as to contribute to the understanding of the tensions of the leaderships within it, during the political proscription period.